The Dynamics of Immature Rubber Photosynthetic Capacities Under Macronutrients Deficiencies - Anasrullah, Anasrullah; Sajjaphan, Kannika; Rattanapichai, Wutthida; Kasemsap, Poonpipope; Nouvellon, Yann; Chura, Dokkeaw; Chayawat, Chompunut; Chotiphan, Rawiwan (Trends in Sciences, 2023)
Pará rubber produces natural latex which is essential for the industries. Rubber plant in immature phase is prone to macronutrient deficiencies due to improper management practices in the field and the nature of immature plants that have sensitive physiological responses under stress conditions. The study aimed to assess the effect of macronutrient limitation on immature rubber trees’ photosynthetic capacity and growth. The immature rubber was pot-grown inside the greenhouse with a completely randomized design experiment and nutrient limitations used as the treatments. The treatments consisted of 5 levels, namely, NPK; NP (-K); NK (-P); PK (-N); Control (-NPK). Photosynthetic capacity parameters (Vc max: maximum rate RuBisCO carboxylation, Jmax: RuBP regeneration rate, and TPU: Triose Phosphate Utilization), tree growth (plant height, flush number, leaf number, stem diameter), and leaf macronutrient (N, P, and K) concentrations were periodically measured. Welsch’s test (α = 0.05) continued with Games-Howell pairwise comparison, followed by Pearson’s correlation test and polynomial regressions were performed to describe the nutrient limitation and photosynthetic capacity relationships. Results showed that the leaf nutrient concentration corresponds with the given treatments, even though it was above the critical level for immature rubber. The limitation of N fertilization slightly reduced plant development and growth such as height, leaf number, flush number, relative growth rate, and photosynthetic capacities. However, the P and K limitation effect could not be observed clearly in the observation periods on growth and photosynthetic capacity parameters. Furthermore, the mobility rate of nutrients from the soil to the plants and its translocation inside plant organs played more essential role in plant growth and photosynthetic capacities. Prolonged observation periods on various rubber clones have to be performed to deeply understand the effects of nutrient deficiencies on immature rubber tree morphophysiological activities. HIGHLIGHTS Rubber plant in immature phase have sensitive physiological responses under stress conditions, and it is prone to macronutrient deficiencies due to improper management practices in the field Assessment of macronutrient limitation effect on immature rubber trees’ photosynthetic capacity and growth is essential to understand how the plants strive under the nutrient scarcity and providing a perspective which nutrient is more essential The N fertilization played more essential role compared to P and K, for immature rubber growth and photosynthetic activity GRAPHICAL ABSTRACT